Perancangan Sistem Informasi Toko Skincare dan Kosmetik Berbasis Website Pada Toko Supramart - Chairunnisa, Shabrina Syifa; Ernawati, Iin (Fakultas Ilmu Komputer, 2025)
Technological advancements and online shopping trends have significantly impacted the beauty industry, particularly in the sale of skincare and cosmetic products. Supramart, established in 2010 and specializing in both local and non-local products, faces various challenges in managing its online sales. In designing this system, an analysis of user and business owner needs was conducted, using the waterfall research flow and the PIECES research method. The key challenges comprise difficulties in effectively introducing products, providing comprehensive product information, and ensuring stock availability. The results of this research led to the design of a website-based information system that can improve sales operational efficiency and customer experience. This system is designed to provide detailed product descriptions, high-quality images, user reviews, and real-time stock information. Furthermore, the system also facilitates promotions and special offers, attracting customer interest and increasing sales. Thus, Supramart is expected to be competitive in the digital market and continue to grow in the future. Through the development of a website-based information system, Supramart is expected to strengthen its position in this dynamic industry and provide better service to customers.